(untitled) (Quaestiones Disputatae: temas en debate, 2022)
Given the use of the category of Citizen Competencies as a proposal of the Ministry of National Education of Colombia (MEN) for citizen training in Colombia, which has its first formulation as a public policy in the year 2003, this research asks about the space that in contains in relation with the notion of otherness, that is developed based on the approaches of Emanuel Levinas. To examine the notion of alterity, which is discovered to be absent, in the proposal of Citizen Competencies, this research analyzes the document Basic Standards of Competencies in Language, Mathematics, Sciences and Citizenship of the MEN (2006). The MEN document will be the object of a discourse analysis with a hermeneutical emphasis, in order to identify the way in which the notion of otherness manifests itself in the State initiative.